28. EFFICACY OF POVIDONE-IODINE GLUCOSE IN THE TREATMENT OF PERFORATED ULCERS (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to compare the effectiveness of Povidone-iodine glucose (PIG) ointment and Povidone-iodine (PI) ointment in the treatment of perforated ulcers and evaluate local and systemic side effects of these two ointments. Materials and methods: 61 patients with perforated ulcers were randomly divided into 2 groups. Group 1 comprised 32 patients treated with Povidone-iodine glucose ointment (PIG group), and group 2 comprised 29 patients treated with Povidone-iodine ointment (PI group). twice daily for 8 weeks. Treatment outcomes were assessed based on ulcer area and ulcer depth every 2 weeks. Drug side effects and patient’s satisfaction was also assessed.Results: At week 2nd, 4th, 6th and 8th, ulcer area reduced 18.2% - 28.9% - 44.4% - 59.4% in the PIG group and 20.8% - 32.9% - 50.9% - 62.7% in the PI group, respectively. The mean reduction in ulcer depth was 0.04 – 0.1 – 0.14 – 0.2cm in PIG group and 0.08 – 0.1 – 0.18 – 0.14 cm in PI group, respectively. The difference in treatment outcomes and side effects between the 2 groups was not statistically significant. After 8 weeks of treatment, in the PIG group, patients with infected ulcers had a better reduction in lesion area than non-infected ulcers (65.9% vs. 52.6%), however, the difference was not statistically significant. Conclusion: In the treatment of perforated ulcers, PIG ointment and PI ointment are equivalent in terms of treatment effectiveness and side effects. Although infected ulcers decreased in lesion area faster when treated with PIG ointment than with PI ointment, the difference was not statistically significant.
Keywords: Chronic ulcer, perforated ulcer, povidone-iodine glucose, betadine.